2003
DOI: 10.1002/app.12374
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyurethane/polyethylene grafted polymers using cyclotriphosphazene as a coupling agent

Abstract: ABSTRACT:The reaction between a dihydroxyphenoxycyclotriphosphazene containing allylic functions, 3, and hexamethylene-1,6-diisocyanate (HDI) leads to a new cyclotriphosphazene-substituted polyurethane 4. The structures of both classes of compounds involved in that synthesis were investigated by 31 P-, 13 C-, and 1 H-NMR, infrared, and mass spectrometries, size-exclusion chromatography, and elemental analysis. The thermal behavior of 4 was investigated and compared to that of hexaphenoxycyclotriphosphazene, N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Researchers substituted its Cl atoms with phenoxy groups to obtain hexaphenoxycyclotriphosphazene (HPCTP), which has been proved to have improved thermal stability [12,13]. Several research groups employed HPCTP to improve the flame retardancy of polyethylene [14], viscose fiber [15], and polystyrene [16].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers substituted its Cl atoms with phenoxy groups to obtain hexaphenoxycyclotriphosphazene (HPCTP), which has been proved to have improved thermal stability [12,13]. Several research groups employed HPCTP to improve the flame retardancy of polyethylene [14], viscose fiber [15], and polystyrene [16].…”
Section: Introductionmentioning
confidence: 99%
“…In respect of fire safety considerations, introducing halogen‐free or phosphorus flame retardants into polymers is an effective way to enhance their flame retardancy . Hexaphenoxycyclotriphosphazene is a typical phosphorus flame retardant with high efficiency and low toxicity, which is often employed to prepare flame retarding polyethylene, polystyrene and viscose fibers . However, researchers have noticed that phosphorus flame retardants are easily enriched in the natural environment, which may induce cancer or cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies on PPZ‐modified PUs have been reported and performed by the use of various approaches. For example, bifunctional hydroxylated or diamined cyclotriphosphazenes were used as chain extenders to prepare poly (cyclotriphosphazene‐urethane)s 16, 17. Another approach was the introduction of PPZ into the PU network 18, 19.…”
Section: Introductionmentioning
confidence: 99%